Efektivitas Konvensi Hak Anak (ICRC) Dalam Kasus Eksploitasi Anak di Thailand : Studi Kasus Tahun 2019-2022 - Syifaturohmah Syifaturohmah; Anifta Dwi Zulianti; Aulia Nur Aisyah; Intan Cahyanengsih; Rika Dwi Mastuti; Lucitania Rizky (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Abstract Child exploitation is one of the most serious cases. Triggered by increasingly advanced and widespread globalization, child exploitation in Thailand continued to increase from 2019 to 2022. As a country that has long ratified the Convention on the Rights of the Child, Thailand's determination to resolve child exploitation cases is questionable. This article examines the effectiveness of the Convention on the Rights of the Child in Thailand from 2019 to 2022, using Arild Underdal's perspective on the effectiveness of the regime and explaining it clearly. The results of this study show that the Convention on the Rights of the Child that has been ratified by Thailand has not yet been fully enforced. This is evidenced by a steady increase every year from 2019 to 2022. This shows that child exploitation cannot be solved with current laws.